PEMBELAJARAN DARING BAGI MAHASISWA DI MASA PANDEMI COVID-19 MENGGUNAKANANALISIS IPA - Cindy Cahyaning Astuti (Universitas Muhammadiyah Tangerang, 2020)
Covid 19 pandemic that occurred in Indonesia certainly had an impact on education sector. Learning online is solution that can be applied in Covid 19 pandemic. Since the Covid-19 pandemic, UMSIDA using 100% online learning. Features available in e-learning are complete and make it easier for lecturers and students to take part in online learning. However, so far no research has been carried out on student responses related to their importance and performance in taking online learning. Based on this, this research will focus on knowing student responses related to interests and performance taking online learning using Important Performance Analysis (IPA). The results using the IPA method showed that, the variables in quadrant I (concentrate here), namely variables X2, X4 and X6 are variables need to be prioritized to improve their quality because these variables are considered important students and are expected to have good performance, but the current condition is still not satisfactory.Keywords: covid-19, e-learning, IPA